Annual report on trade among the member states of the Organisation of Islamic Cooperation 2014-2015 (Islamic Centre for Development of Trade (ICDT) CasablancaMA, 2015)
Presents data on trade among the member states of the Organisation of Islamic Cooperation (OIC).
Keywords: TRADE